2022
DOI: 10.14218/jcth.2021.00336
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Treatment after Transarterial Chemoembolization Failure/Refractoriness: A Review Based on Published Evidence

Abstract: Transarterial chemoembolization (TACE) is widely applied for the treatment of hepatocellular carcinoma. Repeat TACE is often required in clinical practice because a satisfactory tumor response may not be achieved with a single session. However, repeated TACE procedures can impair liver function and increase treatment-related adverse events, all of which prompted the introduction of the concept of "TACE failure/refractoriness". Mainly based on evidence from two retrospective studies conducted in Japan, sorafeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In contrast, a recently published article reviewing the current evidence on subsequent treatment after TACE failure/refractoriness concluded that not only sorafenib, but also other therapies such as TACE with drug-eluting beads, hepatic arterial infusion chemotherapy, ablation, and TACE combined with systemic therapies are potentially useful as subsequent treatment after TACE failure/refractoriness. 47 In addition, a nationwide online survey by the Chinese College of Interventionalists (CCI) in 2020 found an obvious difference in the recognition of TACE failure/refractoriness among Chinese clinicians based on existing definitions. 48 Recently, an expert consensus on TACE refractoriness and subsequent therapies in HCC was published by the CCI.…”
Section: Repeat Tace and Tace Failure/refractorymentioning
confidence: 99%
“…In contrast, a recently published article reviewing the current evidence on subsequent treatment after TACE failure/refractoriness concluded that not only sorafenib, but also other therapies such as TACE with drug-eluting beads, hepatic arterial infusion chemotherapy, ablation, and TACE combined with systemic therapies are potentially useful as subsequent treatment after TACE failure/refractoriness. 47 In addition, a nationwide online survey by the Chinese College of Interventionalists (CCI) in 2020 found an obvious difference in the recognition of TACE failure/refractoriness among Chinese clinicians based on existing definitions. 48 Recently, an expert consensus on TACE refractoriness and subsequent therapies in HCC was published by the CCI.…”
Section: Repeat Tace and Tace Failure/refractorymentioning
confidence: 99%
“…2,6,7 Unfortunately, the efficacy and outcomes of patients receiving systemic therapies alone are still unsatisfactory in clinical practice. 8 Ethical approval: The study was conducted in accordance with the 1964 Declaration of Helsinki and its later amendments and was approved by the Ethics Committee of Jiangsu Cancer Hospital (approval no. 2023-039).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic arterial infusion chemotherapy (HAIC) with fluorouracil, leucovorin, and oxaliplatin (FOLFOX) is a locoregional interventional therapy that can increase local chemotherapeutic drug concentrations to enhance the tumor response rate and reduce systemic toxicity 9,10 and is recommended as one of the first-line options for advanced HCC, especially in patients with portal vein invasion. 11,12 A considerable number of studies have attempted to investigate the efficacy of locoregional treatment with HAIC for HCC when TACE is ineffective or unsuitable, 8,13 while the survival benefits provided by a single HAIC treatment option are also limited and even inferior to those of sorafenib alone. [13][14][15] In recent years, a few studies have demonstrated that combined therapy with HAIC, MTAs, and ICIs has potential therapeutic effects for advanced or TACE-refractory HCC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations